GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 14 Dec 2019, 21:38

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 59725
If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the  [#permalink]

Show Tags

New post 08 May 2018, 01:51
1
3
00:00
A
B
C
D
E

Difficulty:

  45% (medium)

Question Stats:

65% (01:58) correct 35% (02:10) wrong based on 124 sessions

HideShow timer Statistics

Manager
Manager
avatar
P
Joined: 01 Aug 2017
Posts: 220
Location: India
Concentration: General Management, Leadership
GMAT 1: 500 Q47 V15
GPA: 3.4
WE: Information Technology (Computer Software)
Reviews Badge CAT Tests
Re: If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the  [#permalink]

Show Tags

New post 08 May 2018, 02:21
2
The given equation can be changed to
\(14y^2-3y-2=0\)

\(14y^2 - 7y + 4y -2 =0\)

7y (2y-1) + 2 (2y-1) =0

(7y+2) (2y -1) =0

y can be either -2/7 or 1/2.

Ans :- B
e-GMAT Representative
User avatar
V
Joined: 04 Jan 2015
Posts: 3158
Re: If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the  [#permalink]

Show Tags

New post 08 May 2018, 03:59

Solution



Given:
• 2∗\(y^{−2}+3∗y^{−1}\)−14=0

To find:
• The possible value of y

Approach and Working:
• If we assume the value of \(y^{-1}\) to be x, we can rewrite the equation as
    o 2\(x^2\) + 3x – 14 = 0
    Or, 2\(x^2\) + 7x – 4x – 14 = 0
    Or, (x – 2) (2x + 7) = 0
    Or, x = 2 , \(\frac{-7}{2}\)

• Replacing the value of x with y^-1, we can write:
    o \(\frac{1}{y}\) = 2
    Or, y = \(\frac{1}{2}\)
    o Similarly, \(\frac{1}{y} = \frac{-7}{2}\)
    Or, y =\(\frac{-2}{7}\)

As per the options, the correct answer is option B.

Answer: B
_________________
VP
VP
User avatar
D
Joined: 31 Oct 2013
Posts: 1492
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
CAT Tests
Re: If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the  [#permalink]

Show Tags

New post 08 May 2018, 04:04
Bunuel wrote:
If \(2*y^{-2} + 3*y^{-1} - 14 = 0\), which of the following could be the value of y?

A. 2
B. 1/2
C. 2/7
D. -1/2
E. -7


I think back solving will be the easiest way to deal with this question. First simplify the equation the plug in values. B is the correct answer. Here it is clear that fraction will be the correct answer and no negative value won't work. Thus u can't A and E immediately.
SVP
SVP
User avatar
V
Status: It's near - I can see.
Joined: 13 Apr 2013
Posts: 1702
Location: India
Concentration: International Business, Operations
Schools: INSEAD Jan '19
GPA: 3.01
WE: Engineering (Real Estate)
Reviews Badge CAT Tests
Re: If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the  [#permalink]

Show Tags

New post 09 May 2018, 01:38
Bunuel wrote:
If \(2*y^{-2} + 3*y^{-1} - 14 = 0\), which of the following could be the value of y?

A. 2
B. 1/2
C. 2/7
D. -1/2
E. -7



For such questions, back solving is the best and the fastest way.

First simplify the given equation and then try each answer choice.

B is the correct choice.

_________________
"Do not watch clock; Do what it does. KEEP GOING."
Target Test Prep Representative
User avatar
V
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 8701
Location: United States (CA)
Re: If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the  [#permalink]

Show Tags

New post 09 May 2018, 16:45
Bunuel wrote:
If \(2*y^{-2} + 3*y^{-1} - 14 = 0\), which of the following could be the value of y?

A. 2
B. 1/2
C. 2/7
D. -1/2
E. -7


Simplifying we have:

2/y^2 + 3/y - 14 = 0

Multiplying by y^2 we have:

2 + 3y - 14y^2 = 0

14y^2 - 3y - 2 = 0

(7y + 2)(2y - 1) = 0

7y + 2 = 0 → y = -2/7

2y - 1 = 0 → y = 1/2

Since only 1/2 is given as one of the choices. Choice B is the correct answer.

Alternate solution:

If we let x = y^-1, then the equation can be rewritten as 2x^2 + 3x - 14 = 0. Let’s solve it:

(2x + 7)(x - 2) = 0

2x + 7 = 0 → x = -7/2

x - 2 = 0 → x = 2

Since x = y^-1 = 1/y, y = 1/x. Therefore, y is either 1/(-7/2) = -2/7 or 1/2. Since only 1/2 is given as one of the choices. Choice B is the correct answer.

Answer: B
_________________

Scott Woodbury-Stewart

Founder and CEO

Scott@TargetTestPrep.com
TTP - Target Test Prep Logo
122 Reviews

5-star rated online GMAT quant
self study course

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

If you find one of my posts helpful, please take a moment to click on the "Kudos" button.

Senior Manager
Senior Manager
User avatar
G
Joined: 12 Sep 2017
Posts: 308
Re: If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the  [#permalink]

Show Tags

New post 16 Mar 2019, 19:48
ScottTargetTestPrep wrote:
Bunuel wrote:
If \(2*y^{-2} + 3*y^{-1} - 14 = 0\), which of the following could be the value of y?

A. 2
B. 1/2
C. 2/7
D. -1/2
E. -7


Simplifying we have:

2/y^2 + 3/y - 14 = 0

Multiplying by y^2 we have:

2 + 3y - 14y^2 = 0

14y^2 - 3y - 2 = 0

(7y + 2)(2y - 1) = 0

7y + 2 = 0 → y = -2/7

2y - 1 = 0 → y = 1/2

Since only 1/2 is given as one of the choices. Choice B is the correct answer.

Alternate solution:

If we let x = y^-1, then the equation can be rewritten as 2x^2 + 3x - 14 = 0. Let’s solve it:

(2x + 7)(x - 2) = 0

2x + 7 = 0 → x = -7/2

x - 2 = 0 → x = 2

Since x = y^-1 = 1/y, y = 1/x. Therefore, y is either 1/(-7/2) = -2/7 or 1/2. Since only 1/2 is given as one of the choices. Choice B is the correct answer.

Answer: B


Hello ScottTargetTestPrep!!

Whys is it like the follwoing?

14y^2 - 3y - 2 = 0

(7y + 2)(2y - 1) = 0

Shouldn't the sum of the roots be -3?

Regards!
GMAT Club Bot
Re: If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the   [#permalink] 16 Mar 2019, 19:48
Display posts from previous: Sort by

If 2*y^(-2) + 3*y^(-1) - 14 = 0, which of the following could be the

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne